PENGIKATAN GARAM EMPEDU OLEH SUSU KEDELAI TERFERMENTASI DAN STABILITASNYA TERHADAP PEPSIN DAN PANKREATIN [Binding of Bile Salts by Fermented Soymilk and Its Stability Against Pepsin and Pancreatin] - . Yusmarini; Retno Indrati; Tyas Utami; Yustinus Marsono (Jurnal Teknologi dan Industri Pangan, 2013)
ABSTRACT Processed soybean products especially the fermented ones have beneficial health effects since they are capable of reducing the level of plasmacholesterol (hypocholesterolemic effect). One of the mechanisms is by increasing the binding of bile salt. This research was aimed to assess the ability of soymilk, fermented soymilk products and fermented soymilk products combined with enzymatic hydrolysis to bind bile salts. The stability of the binding against hydrolysis by digestive enzymes (pepsin and pancreatin) was also evaluated. Fermented soybean products inoculated with isolates of L. plantarum 1 R.11.1.2 was be able to bind 1.40 μmol/100 mg protein (62.26%) of natrium taurocholate. This binding ability is slightly higher than that of soymilk to natrium taurocholate, i.e.1.33 μmol/100 mg protein (59.04%). Addition of a protease enzyme specific to hydrophobic amino acid (thermolysin) on fermented soymilk products was able to enhance the ability of bind natrium taurocholate. Enzymatic hydrolysis products having a molecular weight of